Japanese Kanji made easy : an easy step-by-step workbook to learn the basic Japanese Kanji (JLPT N5) - Lingo Mastery (Firm). (India : Lingo Mastery ; Repro India Ltd., 2023)
A step-by-stepworkbook to learning and practicing the characters of Japanese Kanji.
People, nature and body parts -- Numbers and time -- Places and directions -- Verbs -- Adjectives -- Let's read and write long sentences.
CSE
Book Finder International
Keywords: Chinese characters -- Japan; Japanese language -- Study and teaching